Power effective induction motors for energy saving; Korus 2005; Vol. 1 - Muravlev (Muravlyov) O. P. Oleg Pavlovich (2005, 2005)
Effectiveness of Russian economy is markedly decreased due to its high power consumption. Nowadays large energy saving potential is accumulated. The purpose of the given work is to examine the potentialities of power effective induction motors design for energy saving. The possibility of induction motor improvement without changing cross section for adjustable electric drives to provide energy saving has been shown. For developing energy saving induction motor it's worth taking into account in optimum criterion not only losses decrease but also expenses decrease of reactive energy compensation and reliability increase which is always observed when active material mass increases.